Catalyst for carbon dioxide hydrogenation reaction as well as preparation method and application thereof
By using boron nitride as a support to interact with active metal components such as iron, manganese, and potassium, an efficient carbon dioxide hydrogenation catalyst is formed, which solves the problems of low reaction activity and insufficient selectivity of existing catalysts, and achieves the effects of high CO2 conversion and low carbon olefin selectivity.
Patent Information
- Application Number
- CN202311369104.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-20
- Publication Date
- 2025-04-22
AI Technical Summary
The existing carbon dioxide hydrogenation catalysts have low reaction activity and low selectivity of low-carbon olefins, resulting in low conversion of carbon dioxide.
Boron nitride is used as a support to interact with active metal components such as iron, manganese, and potassium to form an efficient catalyst. The catalyst is prepared by a solvothermal reaction in one step, which is simple to operate and has low cost.
The activity of carbon dioxide hydrogenation reaction and the selectivity of low-carbon olefins were improved, especially in terms of CO2 conversion and product selectivity of low-carbon olefins.
Smart Images

Figure CN119857511A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of carbon dioxide utilization, and in particular relates to a catalyst for carbon dioxide hydrogenation reaction, a preparation method and application thereof. Background Art
[0002] The gradual increase in global carbon dioxide emissions has caused a series of severe environmental problems such as the greenhouse effect. Therefore, the capture and comprehensive utilization of carbon dioxide (CO2) has received widespread attention. Among them, the hydrogenation of carbon dioxide to produce high-value-added chemicals or liquid fuels is considered to be a very promising research direction. This route can not only reduce the climate and environmental problems caused by carbon dioxide, but also obtain high-value-added chemicals, reducing my country's current dependence on crude oil. Olefins, especially low-carbon olefins (C2-C4), as basic chemical industry raw materials, have important application value and are an important indicator of a country's chemical industry level. my country's low-carbon olefins mainly come from traditional naphtha steam cracking, while my country's oil mainly relies on imports. The high degree of dependence on oil is superimposed on the non-renewable nature of oil. Therefore, the production of low-carbon olefins by hydrogenation of carbon dioxide can increase the source of high-value-added chemicals such as olefins on the one hand, and make important contributions to energy conservation and emission reduction on the other hand.
[0003] Due to the molecular chemical inertness and high thermodynamic stability of carbon dioxide, the activation and selective conversion of carbon dioxide remain extremely challenging problems.
[0004] Patent CN106423263A in the prior art discloses a catalyst for hydrogenating carbon dioxide to produce low-carbon olefins and a preparation method thereof, wherein the catalyst is composed of a metal oxide and a molecular sieve, wherein the metal oxide is composed of ZnO, ZrO2 and a carrier, and the molecular sieve is Or a mixture of HY, the conversion rate of carbon dioxide in this method is low.
[0005] Patent CN108620089A discloses a catalyst for producing low-carbon olefins by hydrogenation of carbon dioxide and a preparation method thereof. The catalyst is an iron-based catalyst with manganese modified on the surface. The method includes hydrothermal synthesis of magnetic Fe3O4 nanospheres and loading different amounts of manganese additives on the surface of the obtained Fe3O4 nanospheres by an impregnation method. The morphology of the catalyst obtained is uniform and controllable, and the reaction stability is good. However, the catalyst preparation process is complicated and requires the addition of a surfactant, resulting in a high catalyst preparation cost.
[0006] Patent CN 113797955 A discloses an iron-magnesium catalyst for hydrogenating carbon dioxide to produce light olefins. The method uses organic amines and ammonium bicarbonate as raw materials, and utilizes ion pair buffering to control the microenvironment of the precipitation process to promote uniform dispersion of iron and magnesium in the catalyst. The method mainly uses pure iron catalysts with a high iron content, so the conversion rate per unit iron is low.
[0007] In recent years, Fe-based Fischer-Tropsch catalysts have attracted extensive attention in the field of preparing light olefins due to their excellent reaction performance and industrial application. However, active metal Fe often has strong interactions with oxide carriers, which easily form difficult-to-reducible substances, resulting in poor activity and selectivity of the catalyst. Correspondingly, weak interactions between the metal and the carrier can easily cause sintering and agglomeration of active components. Summary of the invention
[0008] The purpose of the present invention is to overcome the shortcomings of low reaction activity and low selectivity of low carbon olefins in existing carbon dioxide hydrogenation catalysts, and to provide a catalyst for carbon dioxide hydrogenation reaction, a preparation method and its application. The present invention uses boron nitride that interacts moderately with metal active components iron, manganese and potassium as a carrier, and the catalyst has high carbon dioxide hydrogenation reaction activity and low carbon olefin selectivity, especially high CO2 conversion rate.
[0009] A first aspect of the present invention provides a catalyst for carbon dioxide hydrogenation reaction, comprising a boron nitride carrier and an active metal component supported on the boron nitride carrier, wherein the active metal component comprises iron, manganese and potassium.
[0010] According to some embodiments of the invention, the active metal component consists of iron, manganese and potassium.
[0011] According to some embodiments of the present invention, the catalyst consists of a boron nitride carrier and an active metal component supported on the boron nitride carrier.
[0012] According to some embodiments of the present invention, in the catalyst, the active metal component iron accounts for 5% to 30% of the total mass of the catalyst, preferably 10% to 30%.
[0013] According to some embodiments of the present invention, the active metal component manganese accounts for 0.2-20% of the total mass of the catalyst, preferably 0.5-10%, more preferably 0.5-8%.
[0014] According to some embodiments of the present invention, the active metal component potassium accounts for 0.1% to 5% of the total mass of the catalyst, preferably 0.25% to 3%, and more preferably 0.5% to 3%.
[0015] According to some embodiments of the present invention, the content of the active metal component in the catalyst is based on the mass of the metal element (iron, manganese, potassium).
[0016] According to some embodiments of the present invention, the specific surface area of the boron nitride is preferably 20 to 140 m 2 / g, more preferably 70 to 140 m 2 / g.
[0017] According to some embodiments of the present invention, the boron nitride is hexagonal boron nitride.
[0018] The second aspect of the present invention provides a method for preparing the above catalyst, comprising:
[0019] subjecting a suspension comprising an iron source, a manganese source, a potassium source and boron nitride to a solvothermal reaction;
[0020] According to some embodiments of the present invention, the reaction temperature is 100-200°C.
[0021] According to some embodiments of the present invention, the reaction time is 1 to 24 hours, preferably 6 to 24 hours.
[0022] According to some embodiments of the present invention, the solvothermal reaction is carried out in a hydrothermal synthesis reactor.
[0023] According to some embodiments of the present invention, the mixing method is stirring and / or ball milling; preferably, magnetic stirring or mechanical stirring is used.
[0024] According to some embodiments of the present invention, the preparation method further comprises: after the reaction is completed, washing, centrifuging, drying, and calcining to obtain the catalyst; the drying temperature is preferably 60°C-120°C, and the drying time is preferably 5-24h; and / or the calcination temperature is preferably 300°C-600°C, and the calcination time is preferably 3-12h.
[0025] According to some embodiments of the present invention, the catalyst uses an iron salt as an iron source, a manganese salt as a manganese source, and a potassium salt as a potassium source.
[0026] According to some embodiments of the present invention, the iron salt is selected from one or more of ferric chloride, ferric nitrate, ferrous acetate, ferric oxalate and iron (III) acetylacetonate or hydrates thereof.
[0027] According to some embodiments of the present invention, the manganese salt is selected from one or more of manganese chloride, manganese nitrate, manganese acetate, manganese oxalate and manganese (II) acetylacetonate or their hydrates; the potassium salt is selected from one or more of potassium hydroxide, potassium carbonate and potassium bicarbonate.
[0028] According to some embodiments of the present invention, the solvent used for the iron salt and / or manganese salt is selected from any one or more of the following 1)-3): 1) water; 2) one or more of lower alcohols, N,N-dimethylformamide and toluene; 3) a mixture of water and lower alcohols; preferably, the lower alcohol is selected from one or more of methanol, ethanol, ethylene glycol, and isopropanol, more preferably, the lower alcohol is ethylene glycol; and / or, the solvent used for the potassium salt is selected from one or more of water, methanol, ethanol, ethylene glycol, isopropanol, N,N-dimethylformamide, and toluene.
[0029] According to some embodiments of the present invention, the preparation method further comprises: preparing the suspension,
[0030] Preferably, the process of preparing the suspension specifically includes: mixing a mixed salt solution of iron salt and manganese salt with boron nitride, adding a potassium salt solution, and mixing to obtain the suspension; adding iron salt, manganese salt and potassium salt step by step to avoid the problem that the iron salt, manganese salt and potassium salt are directly mixed and added to react, which easily forms iron hydroxide precipitation and is not conducive to the preparation of the catalyst.
[0031] More preferably, the process of preparing the suspension specifically comprises:
[0032] The mixed salt solution of the iron salt and the manganese salt is mixed with boron nitride and stirred for 2 to 4 hours;
[0033] After adding the potassium salt solution under stirring, stirring is continued for 2 to 4 hours to prepare the suspension.
[0034] According to some embodiments of the present invention, the concentration of the mixed salt solution is 0.05-0.25 mol / L, and the molar ratio of Fe to Mn in the mixed salt is (3.75-20):1, preferably (8-10):1.
[0035] According to some embodiments of the present invention, the potassium salt solution is 0.01 to 0.05 mol / L.
[0036] According to some embodiments of the present invention, the preparation method specifically comprises:
[0037] (1) preparing a mixed salt solution of the iron salt and the manganese salt and the potassium salt solution;
[0038] (2) mixing a mixed salt solution of iron salt and manganese salt with boron nitride;
[0039] (3) adding potassium salt solution and mixing to obtain the suspension;
[0040] (4) The suspension is subjected to a solvothermal reaction.
[0041] According to some embodiments of the present invention, the boron nitride is mixed with the iron source, the manganese source and the potassium source in the form of a boron nitride dispersion to obtain the suspension;
[0042] Preferably, the solvent of the boron nitride dispersion is selected from one or more of water, methanol, ethanol, ethylene glycol, isopropanol, benzene, toluene, N,N-dimethylformamide and N-methylpyrrolidone; preferably ethylene glycol, and the boron nitride dispersion is an ethylene glycol dispersion of boron nitride; the mass concentration of the ethylene glycol dispersion of boron nitride is preferably 1.0 to 3.0 g / L, more preferably 2.0 g / L.
[0043] The third aspect of the present invention provides the use of the above catalyst or the catalyst obtained by the above preparation method in the carbon dioxide hydrogenation reaction;
[0044] According to some embodiments of the present invention, the carbon dioxide hydrogenation reaction is a carbon dioxide hydrogenation reaction to produce light olefins.
[0045] According to some embodiments of the present invention, the temperature of the carbon dioxide hydrogenation reaction is 220°C to 450°C, the reaction pressure is 1.0 to 6.0 MPa, the reaction gas is a mixture of carbon dioxide and hydrogen, and the mass space velocity of the reaction gas is 1000 to 20000 NL kg -1 ·h -1 , a carbon dioxide hydrogenation reaction is carried out in a reactor, and the volume ratio of H2 and CO2 in the reactor is (1-5):1.
[0046] According to some embodiments of the present invention, the catalyst further comprises a step of reducing the catalyst in a reducing atmosphere before catalyzing the carbon dioxide hydrogenation reaction;
[0047] According to some embodiments of the present invention, the reducing atmosphere is hydrogen, the reducing pressure is 0.1-0.5 MPa, the reducing temperature is 280-400° C., and the reducing time is 2-24 h.
[0048] A fourth aspect of the present invention provides a method for preparing light olefins by hydrogenating carbon dioxide, the method comprising: contacting carbon dioxide and hydrogen with the above-mentioned catalyst or the catalyst obtained by the above-mentioned preparation method, wherein the catalyst catalyzes the hydrogenation reaction of carbon dioxide to prepare light olefins.
[0049] Compared with the prior art, the present invention provides a catalyst for carbon dioxide hydrogenation reaction, a preparation method and its application. The present invention uses boron nitride which has moderate interaction with active metal components iron, manganese and potassium as a carrier.
[0050] Therefore, it is of great significance to select a carrier with moderate interaction between metal and carrier to improve the activity and stability of carbon dioxide hydrogenation reaction and improve the product selectivity of light olefins. Boron nitride, as a graphite-like two-dimensional layered material, has the advantages of good thermal conductivity, excellent thermal stability, good corrosion resistance, etc., and after different treatments, it can have a large specific surface area and excellent mechanical properties, and is a good substrate for building composite materials.
[0051] The present invention has the following beneficial effects:
[0052] (1) Boron nitride is used as a carrier in the present invention, and preferably a two-dimensional layered hexagonal boron nitride is used. The carrier of the present invention has the advantages of good thermal conductivity (55W / m K 25℃), excellent thermal stability (air can withstand high temperature of 1000℃), good corrosion resistance, etc., and after different treatments, it can have a large specific surface area and excellent mechanical properties, and is a good substrate for building composite materials. The present invention can prepare a catalyst for carbon dioxide hydrogenation reaction in one step through a simple solvent thermal reaction. The preparation method is simple to operate, has good repeatability, and uses green and cheap raw materials, which is suitable for large-scale production; no template is used in the preparation process, which greatly reduces the introduction of heteroatoms in the catalyst.
[0053] (2) The carbon dioxide hydrogenation catalyst prepared by the present invention fully utilizes the advantages of excellent thermal conductivity and good thermal stability of boron nitride and high reaction activity of iron-based catalysts. The catalyst has the characteristics of easy reduction and carbonization, high CO2 conversion rate and high low-carbon olefin selectivity, and therefore has broad application prospects in carbon dioxide hydrogenation reactions.
[0054] (3) The iron source required for preparing the catalyst of the present invention is cheap and easily available.
[0055] (4) The present invention can significantly improve the reaction performance of the catalyst by adjusting the ratio of metals in the raw materials, thereby providing a new route for the efficient conversion process of carbon dioxide hydrogenation to light olefins. BRIEF DESCRIPTION OF THE DRAWINGS
[0056] Figure 1 This is the XRD pattern of the catalyst prepared in Example 1 of the present invention.
[0057] Figure 2 This is the H2-TPR spectrum of the catalyst prepared in Example 3 of the present invention. DETAILED DESCRIPTION
[0058] The present invention will be further described below in conjunction with specific implementation methods. The protection scope of the present invention is not limited by the following embodiments but is determined by the claims.
[0059] It should be particularly noted that two or more aspects (or implementation methods) disclosed in the context of this specification can be arbitrarily combined with each other, and the technical solution thus formed is part of the original disclosure of this specification and also falls within the scope of protection of the present invention.
[0060] The detection method described in the present invention is a conventional technical method in the art.
[0061] In the embodiments, the carbon dioxide hydrogenation reaction is carried out in one or more fixed bed reactors, microchannel reactors, continuous stirred slurry bed reactors, slurry bubble column reactors or fluidized bed reactors, and is carried out in a continuous or intermittent reaction process.
[0062] The preparation method of the boron nitride and its dispersion is as described in the method disclosed in patent CN112536059A, but is not limited thereto.
[0063] The catalyst evaluation process used in the present invention is as follows:
[0064] A certain amount of catalyst is placed in the constant temperature section of the fixed bed reactor. Before the carbon dioxide hydrogenation reaction, the catalyst is first pretreated and activated in a hydrogen atmosphere at 400°C for 12 hours. After the pretreatment, the reaction system is cooled to 280-360°C, and a synthesis gas (H2 / CO2=(1-5):1) is introduced for reaction evaluation. The mass space velocity is defined as the flow rate of H2 / CO2 synthesis gas per unit mass of catalyst per unit time, and is controlled at 1000-20000NL·kg during the reaction. -1 ·h -1 . CO, CO2, H2, CH4 and C2-C9 hydrocarbons in the gas phase products are quantitatively analyzed by online gas chromatography. During the reaction, the tail gas flow rate is obtained by a wet flow meter and used to calculate the CO2 conversion rate. In one reaction cycle, the cold trap and hot trap are respectively discharged once for component analysis and material balance calculation.
[0065] Example
[0066] Exemplary embodiments of the present invention are described below, including various details of the embodiments of the present invention to aid understanding, which should be considered as merely exemplary. Therefore, it should be appreciated by those of ordinary skill in the art that various changes and modifications may be made to the embodiments described herein without departing from the scope and spirit of the present invention. Similarly, for clarity and simplicity, descriptions of known functions and structures are omitted in the following description. The experimental methods used in the following embodiments are conventional methods unless otherwise specified. The materials, reagents, etc. used in the following embodiments, unless otherwise specified, can all be obtained from commercial sources.
[0067] In the exemplary embodiments of the present invention below, the active metal component is measured by the elemental mass of the metal. Boron nitride is a two-dimensional layered hexagonal boron nitride, which has the advantages of good thermal conductivity (55W / m K 25°C), excellent thermal stability (air can withstand high temperatures of 1000°C), good corrosion resistance, etc.
[0068] The following is a method for preparing a catalyst for carbon dioxide hydrogenation reaction according to an exemplary embodiment of the present invention, comprising the following steps:
[0069] Prepare respectively a mixed salt solution of iron salt and manganese salt, a potassium salt solution and an ethylene glycol dispersion of boron nitride;
[0070] Adding the mixed salt solution of iron salt and manganese salt to the ethylene glycol (boron nitride / ethylene glycol) dispersion of boron nitride, stirring for 2 to 4 hours to obtain a stable and uniform suspension;
[0071] Add the potassium salt solution to the above suspension under stirring conditions, and continue stirring for 2 to 4 hours;
[0072] Subsequently, the obtained suspension is transferred to a hydrothermal synthesis reactor, and the solvent thermal reaction is carried out at 100-200° C. for 1-24 hours. The obtained product is washed, centrifuged, dried, and calcined to obtain the carbon dioxide hydrogenation catalyst.
[0073] Example 1
[0074] Preparation of the catalyst of the present invention and performance test of carbon dioxide hydrogenation
[0075] (1) Dissolve ferric nitrate and manganese nitrate in water at a molar ratio of Fe / Mn of 30:8 (i.e., 3.75:1), stir magnetically until completely dissolved, to obtain a 0.25 mol / L nitrate solution, and prepare a 0.05 mol / L aqueous solution of potassium carbonate.
[0076] (2) 22 mL of the mixed salt solution in step (1) was added dropwise into 500 mL of boron nitride / ethylene glycol dispersion (2 g / L) while mechanically stirring to obtain a stable and uniform suspension.
[0077] (3) Slowly add the aqueous solution of potassium carbonate to the suspension described in step (2) under mechanical stirring and continue stirring for 3 h.
[0078] (4) The suspension in step (3) was transferred to a hydrothermal synthesis reactor and reacted at 180° C. for 12 h. After the reaction was completed, the suspension was naturally cooled to room temperature, washed with deionized water, centrifuged 3 to 5 times, and dried in an oven at 80° C. for 12 h to obtain a dry catalyst precursor.
[0079] (5) The dried catalyst precursor in step (4) is calcined in air at 500° C. for 5 h to obtain the catalyst, wherein the composition of the catalyst is 30Fe8Mn3K / BN; wherein the contents of active metals iron, manganese, and potassium are 30%, 8%, and 3% of the total mass of the catalyst, respectively; except for the active metals, the rest of the catalyst is boron nitride; the surface area of the boron nitride is 140 m 2 / g. The XRD pattern of the catalyst is shown in Figure 1 .
[0080] (6) Carbon dioxide hydrogenation performance test
[0081] The above catalyst (1 g) was placed in the constant temperature section of the fixed bed reactor. The catalyst was reduced in H2 at 400°C and 0.3 MPa for 16 h. After cooling to 220°C, it was switched to synthesis gas (H2 / CO2 = 3, volume ratio), the pressure was increased to 3 MPa, the temperature was slowly increased to 350°C, and the synthesis gas space velocity was 15000 NL kg -1 ·h -1 The carbon dioxide hydrogenation reaction was carried out under the following conditions. The CO2 conversion rate and light olefin selectivity of the reaction are shown in Table 1.
[0082] Example 2
[0083] Preparation of the catalyst of the present invention and performance test of carbon dioxide hydrogenation
[0084] (1) Dissolve ferrous sulfate and manganous sulfate in dimethylformamide at a Fe / Mn molar ratio of 20:1, and stir until they are completely dissolved to obtain a 0.05 mol / L mixed salt solution; and prepare a 0.02 mol / L aqueous solution of potassium hydroxide.
[0085] (2) 42.0 mL of the mixed salt solution in step (1) was added dropwise into 500 mL of boron nitride / ethylene glycol dispersion (2 g / L) while mechanically stirring to obtain a stable and uniform suspension.
[0086] (3) Slowly add the aqueous solution of potassium hydroxide to the suspension described in step (2) under mechanical stirring and continue stirring for 3 hours.
[0087] (4) The suspension in step (3) was transferred to a hydrothermal synthesis reactor and reacted at 140° C. for 24 h. After the reaction was completed, the suspension was naturally cooled to room temperature, washed with deionized water, centrifuged 5 to 8 times, and dried in an oven at 120° C. for 8 h to obtain a dry catalyst precursor.
[0088] (5) The dried catalyst precursor obtained in step (4) is calcined in a helium atmosphere at 450° C. for 8 h to obtain the catalyst, wherein the composition of the catalyst is 10Fe0.5Mn0.25K / BN; wherein the contents of active metals iron, manganese, and potassium are 10%, 0.5%, and 0.25% of the total mass of the catalyst, respectively; except for the active metals, the rest of the catalyst is boron nitride, and the surface area of the boron nitride is 100 m 2 / g.
[0089] (6) Carbon dioxide hydrogenation performance test
[0090] The above catalyst (1 g) was placed in the constant temperature section of the fixed bed reactor. The catalyst was reduced in H2 at 350°C and 0.2 MPa for 16 h. After cooling to 220°C, it was switched to synthesis gas (H2 / CO2 = 2, volume ratio), the pressure was increased to 3.0 MPa, the temperature was slowly increased to 340°C, and the synthesis gas was heated to 5000 NL kg / s at a syngas space velocity of 5000 NL kg / s. -1 ·h -1 The carbon dioxide hydrogenation reaction was carried out under the following conditions. The CO2 conversion rate and light olefin selectivity of the reaction are shown in Table 1.
[0091] Example 3
[0092] Preparation of the catalyst of the present invention and performance test of carbon dioxide hydrogenation
[0093] (1) Dissolve ferrous acetate and manganese acetate in water at a molar ratio of Fe / Mn of 8:1, mix and stir until they are completely dissolved, and obtain a 0.25 mol / L mixed salt solution. Prepare a 0.03 mol / L potassium bicarbonate ethanol solution.
[0094] (2) 21 mL of the mixed salt solution in step (1) was added dropwise into 500 mL of boron nitride / ethylene glycol dispersion (2 g / L) to obtain a stable and uniform suspension.
[0095] (3) Slowly add the ethanol solution of potassium bicarbonate to the suspension in step (2) under mechanical stirring and continue stirring for 3 h.
[0096] (4) The suspension in step (3) was transferred to a hydrothermal synthesis reactor and reacted at 160° C. for 12 h. After the reaction was completed, the suspension was naturally cooled to room temperature, washed with deionized water, centrifuged 3 to 5 times, and dried in an oven at 120° C. for 5 h to obtain a dry catalyst precursor.
[0097] (5) The dried catalyst precursor obtained in step (4) is calcined in an air atmosphere at 400° C. for 8 h to obtain the catalyst, wherein the composition of the catalyst is 20Fe2.5Mn0.8K / BN; wherein the contents of active metals iron, manganese, and potassium are 20%, 2.5%, and 0.8% of the total mass of the catalyst, respectively, and the surface area of the boron nitride is 115 m 2 / g; H2-TPR spectrum of the catalyst is shown in Figure 2 There are two reduction peak positions controlled by H2-temperature program.
[0098] (6) Carbon dioxide hydrogenation performance test
[0099] The catalyst (1 g) was placed in the constant temperature section of a fixed bed reactor. The catalyst was reduced in H2 at 400°C and 0.4 MPa for 24 h. After cooling to 220°C, it was switched to synthesis gas (H2 / CO2 = 4, volume ratio), the pressure was increased to 3.0 MPa, the temperature was slowly increased to 320°C, and the synthesis gas was heated at a space velocity of 10000 NL kg. -1 ·h -1 The carbon dioxide hydrogenation reaction was carried out under the following conditions. The CO2 conversion rate and light olefin selectivity of the reaction are shown in Table 1.
[0100] Example 4
[0101] Preparation of the catalyst of the present invention and performance test of carbon dioxide hydrogenation
[0102] (1) Ferrous oxalate and manganese nitrate were dissolved in water at a molar ratio of Fe / Mn of 10:1, and stirred until they were completely dissolved to obtain a 0.1 mol / L mixed salt solution, and a 0.01 mol / L potassium carbonate ethylene glycol solution was prepared.
[0103] (2) 74 mL of the mixed salt solution obtained in step (1) was added dropwise into 500 mL of boron nitride / ethylene glycol dispersion (2 g / L), while mechanically stirring to obtain a stable and uniform suspension.
[0104] (3) Slowly add the ethylene glycol solution of potassium carbonate to the suspension described in step (2) under mechanical stirring and continue stirring for 4 hours.
[0105] (4) The suspension in step (3) was transferred to a hydrothermal synthesis reactor and reacted at 160° C. for 8 h. After the reaction was completed, it was naturally cooled to room temperature, washed with deionized water, centrifuged 3 to 5 times, and dried at 60° C. for 24 h to obtain a dry catalyst precursor.
[0106] (5) The dried catalyst precursor in step (4) is calcined at 400° C. for 12 h in a nitrogen atmosphere to obtain the catalyst, wherein the composition of the catalyst is 25Fe2.5Mn1.5K / BN, wherein the contents of active metals iron, manganese, and potassium are 25%, 2.5%, and 1.5% of the total mass of the catalyst, respectively, and the surface area of boron nitride is 140 m 2 / g.
[0107] (6) Carbon dioxide hydrogenation performance test
[0108] The catalyst (1 g) was placed in the constant temperature section of a fixed bed reactor. The catalyst was reduced in H2 at 340°C and 0.1 MPa for 16 h. After cooling to 220°C, it was switched to synthesis gas (H2 / CO2 = 2, volume ratio), the pressure was increased to 4.0 MPa, the temperature was slowly increased to 340°C, and the air velocity was 20000 NL kg -1 ·h -1 The carbon dioxide hydrogenation reaction was carried out under the following conditions. The CO2 conversion rate and light olefin selectivity of the reaction are shown in Table 1.
[0109] Example 5
[0110] Preparation of the catalyst of the present invention and carbon dioxide hydrogenation performance test
[0111] (1) Iron (III) acetylacetonate and manganese acetylacetonate were dissolved in toluene at a Fe / Mn molar ratio of 5:1, and stirred until they were completely dissolved to obtain a 0.15 mol / L mixed salt solution; and a 0.02 mol / L potassium carbonate ethylene glycol solution was prepared.
[0112] (2) 52 mL of the mixed salt solution obtained in step (1) was added dropwise into 500 mL of boron nitride / ethylene glycol dispersion (2 g / L) while magnetically stirring to obtain a stable and uniform suspension.
[0113] (3) Slowly add the ethylene glycol solution of potassium carbonate to the suspension described in step (2) under magnetic stirring and continue stirring for 2 h.
[0114] (4) The suspension in step (3) was transferred to a hydrothermal synthesis reactor and reacted at 140° C. for 12 h. After the reaction was completed, the suspension was naturally cooled to room temperature, washed with deionized water, centrifuged 3 to 5 times, and dried at 80° C. for 16 h to obtain a dry catalyst precursor.
[0115] (5) The dried catalyst precursor obtained in step (4) is calcined in nitrogen at 350° C. for 12 h to obtain the catalyst, wherein the composition of the catalyst is 25Fe5Mn2K / BN; wherein the contents of active metal iron, manganese, and potassium are 25%, 5%, and 2% of the total mass of the catalyst, respectively, and the surface area of boron nitride is 130 m 2 / g.
[0116] (6) Carbon dioxide hydrogenation performance test
[0117] The catalyst (1 g) was placed in the constant temperature section of a fixed bed reactor. The catalyst was reduced in a H2 atmosphere at 400°C and 0.3 MPa for 24 h, and then cooled to 220°C, switched to synthesis gas (H2 / CO2 = 3, volume ratio), pressurized to 3.0 MPa, and slowly heated to 320°C. -1 ·h -1 The carbon dioxide hydrogenation reaction was carried out under the conditions of 400 ℃ and 800 ℃, and the CO2 conversion rate and light olefin selectivity of the reaction are shown in Table 1.
[0118] Comparative Example 1
[0119] Boron nitride supported iron-manganese-potassium catalyst prepared by impregnation method and carbon dioxide hydrogenation performance test
[0120] (1) Dissolve ferric nitrate and manganese nitrate in water at a molar ratio of Fe / Mn of 30:8, and stir until they are completely dissolved to obtain a 0.25 mol / L mixed salt solution, and prepare a 0.05 mol / L aqueous solution of potassium carbonate.
[0121] (2) adding a certain amount of the mixed iron-manganese salt solution obtained in step (1) dropwise into the hexagonal boron nitride while continuously stirring for 4 hours to obtain an intermediate product.
[0122] (3) Drying the intermediate product obtained in step (2) in an oven at 80° C. for 12 h to obtain a catalyst precursor.
[0123] (4) taking a certain amount of potassium carbonate aqueous solution, adding it to the above catalyst precursor by impregnation with equal volume, then standing for 6 hours, and drying at 80° C. for 12 hours to obtain a dry catalyst precursor;
[0124] (5) The dried catalyst precursor in step (4) is calcined in air at 500° C. for 5 h to obtain the catalyst, wherein the composition of the catalyst is 30Fe8Mn3K / BN, wherein the contents of active metals iron, manganese and potassium are 30%, 8% and 3% of the total mass of the catalyst, respectively; the specific surface area of the hexagonal boron nitride is 130 m 2 / g.
[0125] (6) Carbon dioxide hydrogenation performance test
[0126] The above catalyst (1 g) was placed in the constant temperature section of the fixed bed reactor. The catalyst was reduced in H2 at 400°C and 0.3 MPa for 16 h. After cooling to 220°C, it was switched to synthesis gas (H2 / CO2 = 3, volume ratio), the pressure was increased to 3 MPa, the temperature was slowly increased to 350°C, and the air velocity was 15000 NL kg -1 ·h -1 The carbon dioxide hydrogenation reaction was carried out under the following conditions. The CO2 conversion rate and light olefin selectivity of the reaction are shown in Table 1.
[0127] Comparative Example 2
[0128] Silica-supported iron-manganese-potassium catalyst prepared by impregnation method and performance test of carbon dioxide hydrogenation
[0129] (1) Dissolve ferric nitrate and manganese nitrate in water at a molar ratio of Fe / Mn of 30:8, and stir until they are completely dissolved to obtain a 0.25 mol / L mixed salt solution, and prepare a 0.05 mol / L aqueous solution of potassium carbonate.
[0130] (2) adding a certain amount of the mixed iron-manganese salt solution obtained in step (1) dropwise to the silicon dioxide while continuously stirring for 4 hours to obtain an intermediate product.
[0131] (3) Drying the intermediate product obtained in step (2) in an oven at 80° C. for 12 h to obtain a catalyst precursor.
[0132] (4) taking a certain amount of potassium carbonate aqueous solution, adding it to the above catalyst precursor by impregnation with equal volume, then standing for 6 hours, and drying at 80° C. for 12 hours to obtain a dry catalyst precursor;
[0133] (5) The dried catalyst precursor in step (4) is calcined in air at 500° C. for 5 h to obtain the catalyst, wherein the composition of the catalyst is 30Fe8Mn3K / SiO2, wherein the contents of active metals iron, manganese and potassium are 30%, 8% and 3% of the total mass of the catalyst, respectively; the specific surface area of the silicon dioxide is 140 m 2 / g.
[0134] (6) Carbon dioxide hydrogenation performance test
[0135] The above catalyst (1 g) was placed in the constant temperature section of the fixed bed reactor. The catalyst was reduced in H2 at 400°C and 0.3 MPa for 16 h. After cooling to 220°C, it was switched to synthesis gas (H2 / CO2 = 3, volume ratio), the pressure was increased to 3 MPa, the temperature was slowly increased to 350°C, and the air velocity was 15000 NL kg -1 ·h -1The carbon dioxide hydrogenation reaction was carried out under the following conditions. The CO2 conversion rate and light olefin selectivity of the reaction are shown in Table 1.
[0136] Comparative Example 3
[0137] Alumina-loaded potassium iron-manganese catalyst prepared by impregnation method and its performance test for carbon dioxide hydrogenation
[0138] (1) Dissolve ferric nitrate and manganese nitrate in water at a molar ratio of Fe / Mn of 30:8, and stir until they are completely dissolved to obtain a 0.25 mol / L mixed salt solution, and prepare a 0.05 mol / L aqueous solution of potassium carbonate.
[0139] (2) adding a certain amount of the mixed iron-manganese salt solution obtained in step (1) dropwise into aluminum oxide while continuously stirring for 4 hours to obtain an intermediate product.
[0140] (3) Drying the intermediate product obtained in step (2) in an oven at 80° C. for 12 h to obtain a catalyst precursor.
[0141] (4) taking a certain amount of potassium carbonate aqueous solution, adding it to the above catalyst precursor by impregnation with equal volume, then standing for 6 hours, and drying at 80° C. for 12 hours to obtain a dry catalyst precursor;
[0142] (5) The dried catalyst precursor in step (4) is calcined in air at 500° C. for 5 h to obtain the catalyst, wherein the composition of the catalyst is 30Fe8Mn3K / Al2O3, wherein the contents of active metals iron, manganese and potassium are 30%, 8% and 3% of the total mass of the catalyst, respectively; the specific surface area of the aluminum oxide is 135 m 2 / g.
[0143] (6) Carbon dioxide hydrogenation performance test
[0144] The above catalyst (1 g) was placed in the constant temperature section of the fixed bed reactor. The catalyst was reduced in H2 at 400°C and 0.3 MPa for 16 h. After cooling to 220°C, it was switched to synthesis gas (H2 / CO2 = 3, volume ratio), the pressure was increased to 3 MPa, the temperature was slowly increased to 350°C, and the air velocity was 15000 NL kg -1 ·h -1 The carbon dioxide hydrogenation reaction was carried out under the following conditions. The CO2 conversion rate and light olefin selectivity of the reaction are shown in Table 1.
[0145] Comparative Example 4
[0146] Preparation of FeMn / BN catalyst and performance test of CO2 hydrogenation
[0147] (1) Ferrous acetate and manganese acetate were dissolved in water at a molar ratio of Fe / Mn of 8:1, and mixed and stirred until they were completely dissolved to obtain a 0.25 mol / L mixed salt solution.
[0148] (2) 21 mL of the mixed salt solution in step (1) was added dropwise into 500 mL of boron nitride / ethylene glycol dispersion (2 g / L) while mechanically stirring to obtain a stable and uniform suspension.
[0149] (3) The suspension in step (3) was transferred to a hydrothermal synthesis reactor and reacted at 160° C. for 12 h. After the reaction was completed, the suspension was naturally cooled to room temperature, washed with deionized water, centrifuged 3 to 5 times, and dried in an oven at 120° C. for 5 h to obtain a dry catalyst precursor.
[0150] (4) The dried catalyst precursor obtained in step (4) is calcined in an air atmosphere at 400° C. for 8 h to obtain the catalyst, wherein the composition of the catalyst is 20Fe2.5Mn / BN; wherein the contents of active metal iron, manganese, and potassium are 20% and 2.5% of the total mass of the catalyst, respectively, and the surface area of the boron nitride is 115 m 2 / g.
[0151] (5) Carbon dioxide hydrogenation performance test
[0152] The catalyst (1 g) was placed in the constant temperature section of a fixed bed reactor. The catalyst was reduced in H2 at 400°C and 0.4 MPa for 24 h. After cooling to 220°C, it was switched to synthesis gas (H2 / CO2 = 4, volume ratio), the pressure was increased to 3.0 MPa, the temperature was slowly increased to 320°C, and the synthesis gas was heated at a space velocity of 10000 NL kg. -1 ·h -1 The carbon dioxide hydrogenation reaction was carried out under the following conditions. The CO2 conversion rate and light olefin selectivity of the reaction are shown in Table 1.
[0153] Comparative Example 5
[0154] Preparation of FeK / BN catalyst and performance test of CO2 hydrogenation
[0155] (1) Dissolve ferrous acetate in water and stir until it is completely dissolved to obtain a 0.25 mol / L mixed salt solution. Prepare a 0.03 mol / L potassium bicarbonate ethanol solution.
[0156] (2) 21 mL of the salt solution in step (1) was added dropwise into 500 mL of boron nitride / ethylene glycol dispersion (2 g / L) while mechanically stirring to obtain a stable and uniform suspension.
[0157] (3) Slowly add the ethanol solution of potassium bicarbonate to the suspension in step (2) under mechanical stirring and continue stirring for 3 h.
[0158] (4) The suspension in step (3) was transferred to a hydrothermal synthesis reactor and reacted at 160° C. for 12 h. After the reaction was completed, the suspension was naturally cooled to room temperature, washed with deionized water, centrifuged 3 to 5 times, and dried in an oven at 120° C. for 5 h to obtain a dry catalyst precursor.
[0159] (5) The dried catalyst precursor obtained in step (4) is calcined in an air atmosphere at 400° C. for 8 h to obtain the catalyst, wherein the composition of the catalyst is 20Fe0.8K / BN; wherein the contents of active metal iron, manganese, and potassium are 20% and 0.8% of the total mass of the catalyst, respectively, and the surface area of the boron nitride is 115 m 2 / g.
[0160] (6) Carbon dioxide hydrogenation performance test
[0161] The catalyst (1 g) was placed in the constant temperature section of a fixed bed reactor. The catalyst was reduced in H2 at 400°C and 0.4 MPa for 24 h. After cooling to 220°C, it was switched to synthesis gas (H2 / CO2 = 4, volume ratio), the pressure was increased to 3.0 MPa, the temperature was slowly increased to 320°C, and the synthesis gas was heated at a space velocity of 10000 NL kg. -1 ·h -1 The carbon dioxide hydrogenation reaction was carried out under the following conditions. The CO2 conversion rate and light olefin selectivity of the reaction are shown in Table 1.
[0162] Comparative Example 6
[0163] Preparation of FeMnK / BN catalyst and performance test of CO2 hydrogenation
[0164] (1) Iron (III) acetylacetonate and manganese acetylacetonate were dissolved in toluene at a Fe / Mn molar ratio of 5:1, and stirred until they were completely dissolved to obtain a 0.15 mol / L mixed salt solution; and a 0.02 mol / L potassium carbonate ethylene glycol solution was prepared.
[0165] (2) 52 mL of the mixed salt solution obtained in step (1) and the ethylene glycol solution of potassium carbonate were added dropwise to 500 mL of boron nitride / ethylene glycol dispersion (2 g / L), and magnetic stirring was performed simultaneously to obtain a stable and uniform suspension, and stirring was continued for 2 h.
[0166] (3) The suspension in step (2) was transferred to a hydrothermal synthesis reactor and reacted at 140° C. for 12 h. After the reaction was completed, the suspension was naturally cooled to room temperature, washed with deionized water, centrifuged 3 to 5 times, and dried at 80° C. for 16 h to obtain a dry catalyst precursor.
[0167] (4) The dried catalyst precursor obtained in step (3) is calcined in nitrogen at 350° C. for 12 h to obtain the catalyst, wherein the composition of the catalyst is 25Fe5Mn2K / BN; wherein the contents of active metal iron, manganese, and potassium are 25%, 5%, and 2% of the total mass of the catalyst, respectively, and the surface area of boron nitride is 130 m 2 / g.
[0168] (5) Carbon dioxide hydrogenation performance test
[0169] The catalyst (1 g) was placed in the constant temperature section of a fixed bed reactor. The catalyst was reduced in a H2 atmosphere at 400°C and 0.3 MPa for 24 h, and then cooled to 220°C, switched to synthesis gas (H2 / CO2 = 3, volume ratio), pressurized to 3.0 MPa, and slowly heated to 320°C. -1 ·h -1 The carbon dioxide hydrogenation reaction was carried out under the conditions of 400 ℃ and 800 ℃, and the CO2 conversion rate and light olefin selectivity of the reaction are shown in Table 1.
[0170] Table 1 Carbon dioxide hydrogenation reaction activity and selectivity of catalysts prepared in Examples 1 to 5 and Comparative Examples 1 to 6
[0171]
[0172] It can be seen from Table 1 that the catalyst prepared by the present invention has a high CO2 conversion rate and a high light olefin selectivity.
[0173] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.
Claims
1. A catalyst for carbon dioxide hydrogenation reaction, characterized in that: The invention comprises a boron nitride carrier and an active metal component supported on the boron nitride carrier, wherein the active metal component comprises iron, manganese and potassium.
2. The catalyst according to claim 1, characterized in that The active metal components consist of iron, manganese and potassium; and / or The catalyst consists of a boron nitride carrier and an active metal component supported on the boron nitride carrier.
3. The catalyst according to claim 1 or 2, characterized in that In the catalyst, the active metal component iron accounts for 5% to 30% of the total mass of the catalyst, preferably 10% to 30%; and / or, The active metal component manganese accounts for 0.2-20% of the total mass of the catalyst, preferably 0.5-10%, more preferably 0.5-8%; and / or, The active metal component potassium accounts for 0.1% to 5% of the total mass of the catalyst, preferably 0.25% to 3%, more preferably 0.5% to 3%; and / or, The content of active metal components in the catalyst is based on the mass of metal elements; and / or, The specific surface area of the boron nitride is preferably 20 to 140 m 2 / g, more preferably 70 to 140 m 2 / g; and / or, The boron nitride is hexagonal boron nitride.
4. A method for preparing the catalyst according to any one of claims 1 to 3, characterized in that: include: A suspension containing an iron source, a manganese source, a potassium source and boron nitride is subjected to a solvothermal reaction.
5. The preparation method according to claim 4, characterized in that The reaction temperature is 100-200°C; and / or, The reaction time is 1 to 24 hours, preferably 6 to 24 hours; and / or, The solvent thermal reaction is carried out in a hydrothermal synthesis reactor; and / or, The mixing method is stirring and / or ball milling; preferably magnetic stirring or mechanical stirring; and / or, The preparation method further comprises: after the reaction is completed, washing, centrifuging, drying, and calcining to obtain the catalyst; the drying temperature is preferably 60° C.-120° C., and the drying time is preferably 5-24 hours; And / or, the calcination temperature is preferably 300° C. to 600° C., and the calcination time is preferably 3 to 12 hours.
6. The preparation method according to claim 4 or 5, characterized in that The catalyst uses an iron salt as an iron source, a manganese salt as a manganese source, and a potassium salt as a potassium source; Preferably, the iron salt is selected from one or more of ferric chloride, ferric nitrate, ferrous acetate, ferric oxalate and iron (III) acetylacetonate or hydrates thereof; and / or, The manganese salt is selected from one or more of manganese chloride, manganese nitrate, manganese acetate, manganese oxalate and manganese (II) acetylacetonate or hydrates thereof; the potassium salt is selected from one or more of potassium hydroxide, potassium carbonate and potassium bicarbonate; and / or, The solvent used for the iron salt and / or manganese salt is selected from any one or more of the following 1)-3): 1) water; 2) one or more of lower alcohols, N,N-dimethylformamide and toluene; 3) a mixture of water and lower alcohols; preferably, the lower alcohol is selected from one or more of methanol, ethanol, ethylene glycol and isopropanol, more preferably, the lower alcohol is ethylene glycol; and / or, the solvent used for the potassium salt is selected from one or more of water, methanol, ethanol, ethylene glycol, isopropanol, N,N-dimethylformamide and toluene.
7. The preparation method according to claim 6, characterized in that: The preparation method further comprises: preparing the suspension, Preferably, the process of preparing the suspension specifically includes: mixing a mixed salt solution of iron salt and manganese salt with boron nitride, adding a potassium salt solution, and mixing to obtain the suspension; More preferably, the concentration of the mixed salt solution is 0.05-0.25 mol / L, and the molar ratio of Fe to Mn in the mixed salt is (3.75-20):1, preferably (8-10):1; and / or, The potassium salt solution is 0.01-0.05 mol / L; and / or, The process of preparing the suspension specifically comprises: The mixed salt solution of the iron salt and the manganese salt is mixed with boron nitride and stirred for 2 to 4 hours; After adding the potassium salt solution under stirring, continue stirring for 2 to 4 hours to prepare the suspension; and / or, The preparation method specifically comprises: (1) preparing a mixed salt solution of the iron salt and the manganese salt and the potassium salt solution; (2) mixing a mixed salt solution of iron salt and manganese salt with boron nitride; (3) adding potassium salt solution and mixing to obtain the suspension; (4) The suspension is subjected to a solvothermal reaction.
8. The preparation method according to any one of claims 4 to 7, characterized in that: The boron nitride is mixed with the iron source, the manganese source and the potassium source in the form of a boron nitride dispersion to obtain the suspension; Preferably, the solvent of the boron nitride dispersion is selected from one or more of water, methanol, ethanol, ethylene glycol, isopropanol, benzene, toluene, N,N-dimethylformamide and N-methylpyrrolidone; preferably ethylene glycol, and the boron nitride dispersion is an ethylene glycol dispersion of boron nitride; the mass concentration of the ethylene glycol dispersion of boron nitride is preferably 1.0 to 3.0 g / L, more preferably 2.0 g / L.
9. Use of the catalyst according to any one of claims 1 to 3 or the catalyst obtained by the preparation method according to any one of claims 4 to 8 in a carbon dioxide hydrogenation reaction; Preferably, the carbon dioxide hydrogenation reaction is a carbon dioxide hydrogenation reaction to produce light olefins; and / or, The temperature of the carbon dioxide hydrogenation reaction is 220°C to 450°C, the reaction pressure is 1.0 to 6.0 MPa, the reaction gas is a mixture of carbon dioxide and hydrogen, and the mass space velocity of the reaction gas is 1000 to 20000 NL·kg -1 ·h -1 , a carbon dioxide hydrogenation reaction is carried out in a reactor, wherein H2 The volume ratio of CO2 is (1-5):1; Preferably, the catalyst further comprises a step of reducing the catalyst in a reducing atmosphere before catalyzing the carbon dioxide hydrogenation reaction; Preferably, the reducing atmosphere is hydrogen, the reducing pressure is 0.1-0.5 MPa, the reducing temperature is 280-400° C., and the reducing time is 2-24 h.
10. A method for preparing light olefins by hydrogenating carbon dioxide, the method comprising: Carbon dioxide and hydrogen are contacted with the catalyst described in any one of claims 1 to 4 or the catalyst obtained by the preparation method described in any one of claims 5 to 8, and the catalyst catalyzes the hydrogenation reaction of carbon dioxide to produce light olefins.
Citation Information
Patent Citations
Fischer-Tropsch Synthesis catalyst containing nitride carrier and preparation method and application thereof
CN107185572A
Catalyst for preparing low-carbon olefin through carbon dioxide hydrogenation as well as preparation method and application of catalyst
CN108620089A
Layered composite material as well as preparation method and application thereof
CN112156784A
Iron oxide / boron nitride nano-catalyst as well as preparation method and application thereof
CN112536059A
Preparation and synthesis method and application of supported iron-based catalyst for preparing liquid fuel through carbon dioxide hydrogenation
CN113649010A